The impact of governance standards on the quality of government health services - Al-Otaibi, Abdan Shaher; Al-Nafie, Meshary Mujahaz; Al-Otaibi, Nawaf Majid; Al-Mutairi, AbdulKarim Moaibed; Al-Otaibi, Muhammad Majid; Al-Ghabiwi, Nayef Saud; Al-Anzi, Abdullah Falah (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the impact of governance standards on the quality of government health services in the Kingdom of Saudi Arabia. To achieve the objectives of the study, the descriptive analytical approach was used. The population of the current study consisted of all workers in health institutions in Riyadh, where the study sample consisted of workers in health institutions in Riyadh. The number of (78) individuals, and the researchers used the questionnaire to collect data, The statistical analysis program spss was used to analyze the study data and in light of the foregoing, the study reached a number of results, the most important of which is that the responses of the study members about the dimensions of the reality of governance standards in the government health sector in the city of Riyadh among the respondents working in health institutions in the city of Riyadh with an arithmetic average ( 3.90), where the averages of their agreement ranged between (4.31 to 3.42), and that the square of the correlation coefficient R square or the coefficient of determination is equal to (0.086) for the independent variable: (governance criteria), and this means that this variable explains (8.6%) of the total variance in Quality of government health services in Riyadh. In the results, the study recommends the need to work on improving the reality of governance standards in the government health sector and strengthening internal control by developing a strategy for its management aimed at transferring the fundamental risks threatening the sector and working to reduce them by developing methods and tools to hedge the government health sector from its negative effects, and continuous coordination of what Between governance management and those in charge of the reality of governance standards in the government health sector, which contributes to achieving the goals of the health sector and adding value to it.
Keywords: Governance Standards; Quality of Health Services; Saudi Health Sector